A new process for separating biofuel based on the salt + 1-butanol + water system. (15th October 2020) - Fu, Chuhan; Li, Zhuoxi; Song, Wenli; Yi, Conghua; Xie, Shaoqu
Highlights: A new process for separating biobutanol. Biobutanol was recovered to the organic phase. Most of water was attracted to the aqueous phase. >97% salt-free biobutanol was obtained. Abstract: Compared with bioethanol, biobutanol with higher energy density and lower vapor pressure is more suitable as a fuel for motor engines. However, the typical low acetone-butanol-ethanol (ABE) concentration hinders the competitiveness of biobutanol because of 1-butanol tolerance. In addition, the dehydration of 1-butanol involves the separation of 1-butanol + water heterogeneous azeotrope, which was usually achieved in a two-column distillation + decantation system. A new process based on the determination of the salt + 1-butanol + water system was proposed to separate biobutanol from a 1-butanol + water system. The salting out resulted in the formation of an organic solvent-rich phase and an aqueous phase. All the 1-butanol in the water-rich phase was recovered to the organic phase, and most of the water in the 1-butanol-rich phase was attracted to the aqueous phase by the salting-out effects of the electrolytes, namely potassium carbonate, dipotassium hydrogen phosphate, tripotassium phosphate, and potassium pyrophosphate. This effect produces a top phase containing greater than 97% salt-free 1-butanol. The salting-out effect, the solubility, and the solvation effect of an electrolyte play essential roles in the separation of 1-butanol.